Composição do leite como indicador metabólico- nutricional em bovídeos a pasto - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The composition of milk is used to evaluate the metabolism of cattle that are fed on pasture, enabling better performance and productivity. High levels of protein in the diet tend to release ammonia into the rumen, which will lead to high levels of urea nitrogen in milk, resulting in variations in productive and reproductive efficiency, increased production costs and negative impacts on the environment. Therefore, the objective of this work was to evaluate the levels of urea nitrogen, physical-chemical composition and somatic cell count of milk produced in the São Francisco do Caramuri Community, located in Baixo Rio Preto da Eva, seeking to estimate analysis methods that can be used by rural producers in Amazonas due to the better quality of milk and dairy products. In this way, the production of 61 dairy cattle and 29 dairy buffaloes were analyzed during periods of drought and flood of rivers. The assessment of urea nitrogen in milk can identify the low efficiency of urea nitrogen use by cows. Therefore, adjustments implemented in the diet can result in greater production of these animals or savings in nutrients, especially protein, which is one of the most expensive ingredients, providing greater profit to the producer.
Keywords: .; .; .; CIENCIAS AGRARIAS: ZOOTECNIA: PRODUCAO ANIMAL; Análise; Eficiência; Produção; Ruminantes